Kaisa: Jurnal Pendidikan dan Pembelajaran: Pengembangan Pop Up Book "Pop Soda" Berbasis Powerpoint Untuk Pembiasaan Sedekah di PAI Kelas 2 SD - Destyana Azizah; Romlah, Siti; Nisa, Viny Khoirun; Aeni, Ani Nur (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2025)
To improve students' understanding of the concept of almsgiving in PAI learning in elementary schools, this study suggests creating a PowerPoint-based digital Pop Up Book called POP SODA. This research was conducted on grade 2 students of MI Annur 4 in Malangbong, Garut, using a systematic D & D (Design and Development) approach with the ADDIE model. The focus of this research is to find out how effective the PowerPoint-based digital Pop Up Book media is available for use in elementary schools. The results showed that the digital media Pop Up Book “POP SODA”, which consists of a PowerPoint presentation, has great potential to improve students' understanding of the concept of almsgiving. This digital pop up book, which uses Microsoft PowerPoint, provides an interactive and fun learning experience for students. The product serves as an effective learning tool, as indicated by the positive responses from students and evaluations from experts. Therefore, the use of technology in education, particularly in PAI learning, is becoming increasingly important to ensure that learning is relevant and engaging. The digital Pop Up Book “POP SODA” comes as a step forward to address the difficulties students face in conveying abstract concepts. It offers an innovative and successful approach to PAI learning in elementary schools.